Breit interaction overtaking Coulomb force at low energies: an unexpectedly efficient mechanism for ionization in slow collisions - A Jacob; C Müller; A B Voitkiv (New Journal of Physics, 2024)
It is generally assumed that ionization in slow collisions of light atomic particles, whose constituents (electrons and nuclei) move with velocities orders of magnitude smaller than the speed of light, is driven solely by the Coulomb force. Here we show, however, that the Breit interaction—a relativistic correction to the Coulomb interaction between electrons—can become the main actor when the colliding system couples resonantly to the quantum radiation field. Our results demonstrate that this ionization mechanism can be very efficient in various not too dense physical environments, including stellar plasmas and atomic beams propagating in gases.